2023
DOI: 10.1590/2175-8239-jbn-2022-0149en
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization and mortality during the pandemic in chronic hemodialysis patients and the general population in Peru

Abstract: Background: Patients with chronic kidney disease have a higher risk of severe disease and mortality from COVID-19 than the general population. Objective: To compare hospitalization and mortality rates during the pandemic among chronic hemodialysis (HD) patients and the general population in Lima (Peru). Methods: This retrospective cohort included an assessment of the database of chronic HD patients of the health service providers of the social health insurance benefit networks of Lima and Callao between 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In respect to short-term outcomes related to COVID-19 infection, according to Herrera-Anazco et al, dialysis patients showed higher rates of admission to hospital and mortality rates after COVID infection, compared with the remaining of population [30]. Other authors supported these ndings [4,5].…”
Section: Discussionmentioning
confidence: 91%
“…In respect to short-term outcomes related to COVID-19 infection, according to Herrera-Anazco et al, dialysis patients showed higher rates of admission to hospital and mortality rates after COVID infection, compared with the remaining of population [30]. Other authors supported these ndings [4,5].…”
Section: Discussionmentioning
confidence: 91%